Carrier detection and early diagnosis of Wilson's disease by restriction fragment length polymorphism analysis. Issue 2 (February 1989) - Figus, A; Lampis, R; Devoto, M; Ristaldi, M S; Ideo, A; de Virgilis, S; Nurchi, A M; Corrias, A; Corda, R; Lai, M E
Abstract : Wilson's disease, a rare autosomal recessive disorder, has been recently mapped to the long arm of chromosome 13 (q14.1). In this study, we carried out linkage analysis between three chromosome 13 DNA markers, D13S1, D13S10, D13S2, the locus for the red cell enzyme esterase D (ESD), and the Wilson's disease locus (WND) in 17 Wilson's disease families of Italian descent, mostly from Sardinia. We confirmed a tight linkage [theta = 0.00, Z (theta) = 4.07] between the WND and ESD loci, and provided suggestive evidence for linkage [theta = 0.00, Z(theta) = 1.85] of the WND locus with D13S10. Multipoint linkage analysis indicated the following order: centromere-D13S1-D13S10-WND-ESD-D13S2. RFLP analysis at these two loci in our families allowed us either to define the carrier status (50%) or to exclude the homozygous state (25%) in the great majority of unaffected sibs.